Republic of Poland : Technical Assistance Report-Developing a Medium-Term Budget Framework. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the progress made toward developing a medium-term budget framework (MTBF) in Poland. Many of the prerequisites for establishing an MTBF have already been satisfied in Poland. The annual budget has a high degree of credibility; macroeconomic projections are generally accurate; and fiscal rules on debt, expenditure, and the deficit provide sufficient guidance to fiscal policy in the medium term. However, some weaknesses remain that should be addressed either in parallel or as part of the MTBF reform. The design of the MTBF should be carefully considered to meet the government's fiscal objectives while operating within current capabilities.